Hospital Outcomes of Surgical Closure of Patent Ductus Arteriosus: 19 Years Experience at Shahid Gangalal National Heart Center - Koirala, R.; Panthee, N.; Pradhan, S.; Rajbhandari, N.; Shrestha, D.K.; Chhetri, S.; Shrestha, Y.; Dahal, A.; Dhakal, S.; Thapa, S. (Kathmandu University Medical Journal, 2020)
Background Ductus arteriosus is a vascular structure which connects the roof of main pulmonary artery near the origin of the left branch pulmonary artery to the proximal descending aorta. Patent ductus arteriosus (PDA) closure is indicated for any patient who is symptomatic from left to right shunting.Objective To investigate the hospital outcomes of surgical closure of patent ductus arteriosus over last 19 years starting from the very first case of our center.Method This is a retrospective analysis of all patent ductus arteriosus treated surgically from August 2001 to July 2019. Patients who underwent isolated surgical closure of patent ductus arteriosus were included. Data have been presented in three different eras (Era 1: 2001-2007, Era 2: 2008-2013, and Era 3: 2014-2019) to see the trend of evolution of this surgery.Result A total of 901 patients aged 8.67±8.76 years under went patent ductus arteriosus surgical closure over last 19 years. Patients in the initial era 2001-2007 were significantly older compared with other 2 eras (p=0.000). Males accounted for 35.5% of all cases. Twenty percent had severe pulmonary artery hypertension. Duration of mechanical ventilation was 3.57±9.64 hours with ICU stay of 1.55±1.53 days, and hospital stay of 3.9±2.3 days. Overall in hospital mortality was 0.8%; for isolated patent ductus arteriosus diagnosis, mortality was 0.2%. Chylothorax was noted in 0.4%.Conclusion This is the first report to analyze surgical outcomes of patent ductus arteriosus ligation in our center. We have discussed the evolution of patent ductus arteriosus surgery in our center, and have shown favorable outcomes in terms of morbidity and mortality.